Media Komik Digital Berorientasi Sosio-Kultural Tri Hita Karana Untuk Meningkatkan Literasi Budaya Peserta Didik Pada Topik Warisan Budaya Kelas V SD. - I Gede Adi Sanjaya; I Ketut Suma (Universitas Pendidikan Ganesha, 2025)
Cultural literacy is a crucial skill that every individual should possess. However, the implementation of literacy, particularly in Indonesia, remains relatively low based on various sources and field findings. Therefore, this research aims to develop a learning media to enhance students' cultural literacy. The development of this learning media employs the Research and Development (R&D) method to produce a media that is valid, practical, and effective in improving students' cultural literacy. Based on the findings, the total Content Validity Ratio (CVR) obtained from the validity test is 42.00 with 42 items and a Content Validity Index (CVI) of 1.00, indicating that the media is valid. Furthermore, the practicality test based on responses from teachers and students yielded indices of 95% and 98% respectively, signifying that the media is highly practical. Lastly, the effectiveness of the media, based on the analysis of One Group Pre-Test Post-Test, showed a significance level of <0.01, indicating that the media is highly effective in enhancing students' cultural literacy. After conducting the research, a valid, practical, and effective digital comic media has been developed to improve students' cultural literacy. The implication of developing socio-culturally oriented Tri Hita Karana digital comic learning media is the availability of audiovisual media that is relevant to learning needs in the era of the Merdeka Curriculum, especially in elementary schools, and is able to accommodate the learning profiles of students with visual and auditory learning styles.